MODEREASI RETURN ON ASET PADA DETERMINAN INTELECTUAL CAPITAL - Rahmat Hidayat; Edisah Putra Nainggolan (Jurnal Ilmiah Global Education, 2023)
This study aims to analyze the moderation of return on assets on the factors that influence the disclosure of Intellectual Capital in industrial companies listed on the Indonesia Stock Exchange. The determining factors are company size and managerial ownership. The analysis technique used is multiple linear regression analysis. The results show that partially company size has an effect on Intellectual Capital disclosure, managerial ownership has an effect on Intellectual Capital disclosure, Return on Assets moderates the effect of company size and managerial ownership on Intellectual Capital disclosure, in Industrial companies which are listed on the Indonesia Stock Exchange